Integration and learning: a case study of the international higher physical education talent-cultivation model - Song, Bruce; Xi, Jun; Li, Shichen; Zhou, Yuan; Zhang, Qiangfeng; Zhou, Huixuan; Feng, Chen; Grecic, David; Peng, Xiyang (Frontiers in Education, 2024)
Physical education (PE), a crucial emerging discipline, has received enormous attention from the Chinese government and educational administrations. The release of the 'powerful sports nation' outline and the promotion of Chinese national policies such as the 'integration of sports and education' have increased the strategic status of higher PE, making it a crucial supplement to higher education in China. This study employed mixed-method research based on the characteristics of cooperative educational institutions in China and Britain to explore the concepts and experiences of internationalised sports talent training. It represents the world's first off-site sports talent-training model and the first fullscale introduction of a pilot higher PE programme in China. By combining the CARE education concept and the 'five concentrations' talent-cultivation model, we analysed the qualitative data and quantitative research results. Further, we constructed a model of the cooperative Sino-foreign system for cultivating talent through PE. Our results indicated that the cultivation of talents via PE based on the cooperative educational system must focus on constructing unique educational objectives and talent-cultivation concepts, constructing a standardised teaching system, introducing external high-quality educational resources, localising external resources, and the organic integration of the partner's educational system. Based on these results, we presented a pilot-unitintegrated model of Chinese and foreign talent cultivation, offering a theoretical reference for subsequent research and educational practice.